The Monopoly of Technique: Gender Inequalities and Female Agency in Support Work in the Chilean Musical Field [el Monopolio de la Técnica: Inequidades de Género y Agencia Feminista en Las Labores de Apoyo del Campo Musical Chileno] - Valdovinos-Suazo, M (Pontificia Universidad Catolica de Chile, 2021)
This article investigates how gender inequalities are expressed in the technical domains of the music world, a highly relevant domain of the music field which has not received sufficient attention from the sociology and history of art and music. This qualitative study, based on in-depth interviews and focus groups, discusses the conceptual contributions of gender theory to document what it means for women to perform in the masculinized context of support work in the music field. We explore the subjective costs and the daily barriers of gender inequalities. This text also seeks to make visible the resources and strategies that women deploy to develop their careers in the music field, namely using alternative ways of building teams in an adverse context. Finally, it is concluded that the technical environment is highly masculinized, which severely limits women s professional possibilities. In this scenario, women and the LGBTQ community have progressively broken ground and demonstrated other ways of doing things. © 2021 Authors. All rights reserved.